Corrosion experiment method for synchronously observing corrosion rate and structure

By performing dissolution simulation experiments on cylindrical slices and special-thick rock sheets under high temperature and high pressure conditions, the problem that the existing technology cannot simultaneously observe dissolution rate and structural changes is solved, and synchronous observation of dissolution rate and structural changes is achieved, which is of great theoretical and practical significance.

CN119667110APending Publication Date: 2025-03-21PETROCHINA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311219932.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing carbonate karst dissolution simulation experiments cannot simultaneously observe dissolution rate and rock structure changes, and cannot monitor the dissolution process in real time. In addition, three-dimensional CT can only see the changes in pore space, and cannot synchronize the impact of rock formation on dissolution pore formation and evolution process.

Method used

A dissolution experimental method is adopted to synchronize dissolution rate and structure observation. By performing dissolution simulation experiments on cylindrical slices and special-thick rock sheets under high temperature and high pressure conditions, the parameters and microscopic characteristics before and after dissolution are recorded, and synchronous observation of dissolution rate and structural changes are achieved.

Benefits of technology

The quantification of dissolution rate and the visualization of the preferred dissolution parts of rocks can be achieved, and it is of great theoretical and practical significance to understand the dissolution law, understand the erosion formation process of reservoir pores, and predict the distribution of pores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004460278540000091
    Figure BDA0004460278540000091
  • Figure HDA0004460278740000011
    Figure HDA0004460278740000011
  • Figure HDA0004460278740000021
    Figure HDA0004460278740000021
Patent Text Reader

Abstract

The invention discloses a corrosion experiment method for synchronously observing the corrosion rate and the structure, and belongs to the technical field of oil and gas reservoir geological experiment analysis. According to the method disclosed by the invention, in the corrosion experiment process, rock slices and slices are recorded to be subjected to the corrosion experiment at the same time, the experiment result has a corrosion quantitative index, namely the corrosion rate, the corrosion structure change can be mastered, the corrosion rule can be understood more comprehensively, and the corrosion pore and crack formation and evolution process can be accurately known; the defect that only the corrosion rate change can be obtained and the preferential corrosion part of the rock cannot be observed in the conventional corrosion experiment is overcome, the rock corrosion rate quantification and the preferential corrosion part visualization of the rock are realized, and the method has important theoretical and practical significance for knowing the formation process of reservoir hole corrosion and predicting hole distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of geological experimental analysis of oil and gas reservoirs, and in particular relates to a dissolution experimental method for synchronously observing dissolution rate and structure. Background Art

[0002] Carbonate oil and gas reservoirs account for more than 50% of the world's oil and gas production. The formation of carbonate reservoir space is often related to secondary dissolution on the surface or during burial. Therefore, in order to understand the formation and evolution of reservoir space, carbonate dissolution simulation experiments are the most important means and have become a hot topic for petroleum geologists. Through simulations of different dissolution conditions, the formation mechanism, evolution process and control factors of carbonate reservoirs can be effectively analyzed, and the laws of reservoir development can be mastered, thereby guiding the exploration and development of oil and gas reservoirs. The most important parameters for characterizing the degree of dissolution in dissolution experiments are dissolution amount, dissolution rate, and structural changes before and after dissolution.

[0003] The early carbonate rock dissolution simulation experimental technology was relatively simple, and it mostly focused on the relationship between factors such as temperature and pressure and the amount of carbonate rock dissolution. Using the dissolution rate experiment of a single mineral, such as comparing the dissolution rates of calcite and dolomite; or comparing the dissolution amount of different types of carbonate rocks under the same fluid properties. In the 1980s, domestic and foreign scholars mainly studied the dissolution mechanism of carbonate rocks in deep burial environments. The experimental method used the surface reaction between fluids and rock particles or blocks. Through the change in dissolution amount, combined with standard test pieces, the carbonate rock dissolution rate can be calculated. For example, the simulation experiment ("Experimental simulation of the dissolution and diagenesis process of carbonate rocks of different compositions under temperature and pressure conditions of supergene and burial diagenesis", 1995) conducted dissolution experiments of oolitic dolomite, microcrystalline dolomite, dolomite limestone, and dolomite-bearing limestone with acetic acid under three different temperature and pressure conditions. The results show that: ① Under the temperature and pressure conditions of surface and relatively shallow burial (below 75℃, 20MPa), the dissolution rate of calcite is much higher than that of dolomite. With the increase of temperature and pressure, the difference in the dissolution rates of the two becomes smaller. ② Under the temperature and pressure conditions of relatively deep burial (above 75℃, 20MPa), the dissolution rate of dolomite has exceeded that of calcite. Fan Ming (“The transformation effect of acidic fluids on carbonate reservoirs”, 2009) of Wuxi Petroleum Geology Research Institute of Sinopec conducted a study on the transformation of carbonate reservoirs with three acidic fluids (acetic acid solution, CO 2 Aqueous solution and H 2 S aqueous solution) were used to conduct dissolution comparison experiments with six types of carbonate rocks (oolitic dolomite, oolitic limestone, microcrystalline dolomite, microcrystalline limestone, microcrystalline limestone, and microcrystalline dolomite limestone). The results show that: ① As the temperature rises from room temperature to 200℃, the dissolution ability of organic acids on carbonate rocks changes from weak to strong and then to weak, and the dissolution ability is strongest at around 90℃; ② CO 2The dissolution capacity of aqueous solution on carbonate rocks has a strong → strong → weak trend, and the maximum dissolution rate is between 60℃-90℃. Although the above experiments can measure the difference in dissolution rate of different carbonate rocks, the change of dissolution structure cannot be observed.

[0004] Therefore, Fang Yang and others from China University of Geosciences (Beijing) used rock slices and scanning electron microscopes to observe the changes in dissolution structure before and after dissolution (Geochemical dissolution of oolitic carbonate rocks based on rock slices, 2016), but unfortunately, the dissolution rate could not be calculated. In 2015, the patent CN104407118A of the Hangzhou Institute of Geology of PetroChina provided a carbonate rock internal dissolution reaction device, which quantitatively analyzed the dissolution rate and dissolution structure changes before and after the reaction by comparing the weight, pore volume, permeability, 3D CT pore structure characteristics, pore throat parameter statistics, microscopic dissolution morphology characteristics of carbonate rocks before and after the experiment, and the changes in the composition of the carbonate rock reaction liquid under the corresponding temperature and pressure conditions. However, the device is an experiment and cannot achieve real-time monitoring during the experiment. In addition, the 3D CT can only see the changes in pore space, and cannot observe the influence of rock structure on pore space changes. Therefore, the rock structure cannot be synchronously observed for the formation of dissolution pores and the pore evolution process and dissolution rate changes in the experiment. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a dissolution experimental method for synchronously observing the dissolution rate and structure, so as to solve the technical problem that previous dissolution experiments can only obtain the change of dissolution rate but cannot observe the defects of the preferential dissolution parts of the rock.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention discloses a dissolution experimental method for synchronously observing dissolution rate and structure, comprising the following steps:

[0008] S1: Analyze the actual geological background, determine the simulated experimental samples and prepare the experimental fluid;

[0009] S2: Process the determined simulated experimental samples into cylindrical slices and rock thin sections of special thickness respectively; then measure and calculate the parameters of each cylindrical slice.

[0010] S3: Record the surface morphology and microscopic features of cylindrical slices and rock thin sections of special thickness respectively;

[0011] S4: After subjecting the cylindrical slices and rock slices of special thickness in S2 to dissolution simulation experiments with different reaction times in the prepared experimental fluid, the parameters of the cylindrical slices after the dissolution simulation experiments with different reaction times are measured and calculated to obtain the dissolution rate per unit area of ​​the cylindrical slices with different reaction times; the surface morphology and microscopic characteristics of the rock slices of special thickness after the dissolution simulation experiments with different reaction times are recorded.

[0012] Furthermore, in S1, the actual geological background includes petrological parameters and geological fluid characteristics of the carbonate reservoir.

[0013] Furthermore, simulation test samples are determined according to petrological parameters of the carbonate reservoir.

[0014] Furthermore, the petrological parameters of the carbonate reservoir are rock type, mineral composition, pore type and pore structure.

[0015] Furthermore, experimental fluid is prepared according to the characteristics of geological fluid.

[0016] Furthermore, in S2, the diameter of the cylindrical slice is 2.5 to 3 cm, and the thickness is 3 to 5 mm; the thickness of the special thickness rock slice is 100 to 300 μm.

[0017] Furthermore, the parameters are the weight and surface area of ​​the cylindrical slices.

[0018] Furthermore, before measuring the weight of the cylindrical slice, the cylindrical slice is washed with ultrapure water and then dried;

[0019] The calculation process of the surface area of ​​the cylindrical slice is as follows: the diameter and thickness of each cylindrical slice at different positions are measured with a vernier caliper, and the average value of the diameter and thickness is obtained, and then the surface area of ​​each cylindrical slice is calculated.

[0020] Furthermore, the microscopic characteristics include mineral composition, surface structure, pores and crack development; the surface morphology is obtained by observing with a polarizing microscope.

[0021] Furthermore, in S4, the temperature of the dissolution simulation experiment is 50-100° C., the pressure is 0.1-0.4, and the time is 1-240 hours.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention discloses a dissolution experimental method for synchronous observation of dissolution rate and structure. On the basis of using rock test pieces as dissolution objects, through multiple experiments, a rock thin section with special thickness is invented. At the same time, the present invention provides a method for simultaneously conducting high-temperature and high-pressure dissolution experiments on the two. This method overcomes the defect that previous dissolution experiments can only obtain changes in dissolution rate, but cannot observe the preferential dissolution sites of rocks, and realizes the quantification of rock dissolution rate and visualization of preferential dissolution sites of rocks. It has important theoretical and practical significance for understanding the formation process of reservoir pore dissolution and predicting pore distribution. During the dissolution experiment, this method records rock slices and thin sections and conducts dissolution experiments at the same time. The experimental results have both dissolution quantitative indicators - dissolution rate, and can grasp the changes in dissolution structure, so that the dissolution law can be understood more comprehensively to accurately understand the formation and evolution process of dissolution pores and cracks. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A flow chart of the dissolution experimental method for simultaneous observation of dissolution rate and structure of the present invention;

[0025] Figure 2 This is a typical core photo of the simulated experimental sample in Example 1 of the present invention;

[0026] Among them: a-GS1, algae calcite dolomite; b-GS2, algae stromatolite siliceous dolomite; c-GS3, algae stromatolite; d-MX4, fine-medium crystalline dolomite; e-MX1, algae-containing dolomite, algae content is about 10%; f-MX2, algae clot dolomite, algae content is greater than 50%; g-MX3, algae clot dolomite, algae content is greater than 70%;

[0027] Figure 3 The curve of dissolution rate changing with time obtained by the method of the present invention;

[0028] Among them: a-GS1, algae-containing dolomite; b-GS2, algae-containing siliceous dolomite; c-GS3, algae-containing dolomite; d-MX1, algae-containing dolomite, the algae content is about 10%; e-MX2, algae-containing dolomite, the algae content is greater than 50%; f-MX3, algae-containing dolomite, the algae content is greater than 70%; g-MX4, fine-medium crystalline dolomite; h-HD1, fine-crystalline dolomite;

[0029] Figure 4 Schematic diagram of photos of cylindrical slice samples obtained by the method of the present invention before and after dissolution;

[0030] Among them: a-before the experiment, GS1, algal sand-clastic dolomite; b-after the experiment, GS1, algal sand-clastic dolomite; c-before the experiment, GS2, algal stromatolitic siliceous dolomite; d-after the experiment, GS2, algal stromatolitic siliceous dolomite; e-before the experiment, GS3, algal stromatolitic dolomite; f-after the experiment, GS3, algal stromatolitic dolomite; g-before the experiment, MX4, fine-medium crystalline dolomite; h-after the experiment, MX4, fine-medium crystalline dolomite;

[0031] Figure 5 The changing characteristics of the algae-layered siliceous dolomite obtained by the method of the present invention after different dissolution times;

[0032] Among them: a-before the experiment, GS2, algae-layered siliceous dolomite, the red circle is microcracks; b-before the experiment, GS2, algae-layered siliceous dolomite, the red circle is dolomite grains; c-before the experiment, GS3, algae-layered dolomite; d-after the experiment, GS2, algae-layered siliceous dolomite, microcracks expand and dissolve; e-after the experiment, GS2, algae-layered siliceous dolomite, dolomite grains dissolve; f-after the experiment, GS3, algae-layered dolomite, the sample surface becomes blurred;

[0033] Figure 6 The change characteristics of algae clot dolomite obtained by the method of the present invention after different dissolution times;

[0034] Among them: a-before the experiment, MX3, algae clot dolomite; b-5h after the experiment, MX3, algae clot dolomite; c-12h after the experiment, MX3, algae clot dolomite; d-18h after the experiment, MX3, algae clot dolomite. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0036] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0037] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0038] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0039] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0040] The present invention provides a dissolution experimental method for synchronously observing dissolution rate and structure, comprising the following steps:

[0041] S1: Detect the petrological parameters, geological fluid characteristics and geological background parameters of the carbonate reservoir in the simulated experimental area, analyze the actual geological background, select samples for simulation experiments based on the test results, and configure fluids that meet the geological background;

[0042] S2: Process the determined simulated experimental samples into cylindrical slices (thickness reaches 3-5 mm) and special thickness rock slices (thickness reaches 100-300 μm); the special thickness rock slices can ensure optical observation under a polarizing microscope and ensure that the rock slices are not completely dissolved to affect the dissolution reaction; then measure and calculate the parameters of each cylindrical slice;

[0043] The parameters include the weight and surface area of ​​the cylindrical slices; the diameter and thickness of each cylindrical slice at different positions are measured with a vernier caliper, and the average value is calculated to calculate the surface area of ​​each cylindrical slice; the cylindrical slices are washed with ultrapure water and dried in a constant temperature drying oven at 105°C for 2 hours; after drying, the samples are cooled in a drying dish, and the mass of each cylindrical slice is weighed with an analytical balance;

[0044] S3: Record the surface morphology and microscopic features of cylindrical slices and rock slices of special thickness respectively; take photos of each cylindrical slice with a camera; observe the microscopic features of each cylindrical slice and rock slice of special thickness with a polarizing microscope, including composition, structure, pores and crack development;

[0045] S4: Place the cylindrical slices and thin slices of each sample in the same beaker, pour in the configured experimental fluid, then place the beaker in a rotary high-temperature and high-pressure reactor, set the experimental temperature and pressure to conduct the dissolution experiment; after the dissolution experiment is carried out for different time periods, take out the samples, measure and calculate the parameters of several cylindrical slices after the dissolution experiments with different reaction times, and obtain the dissolution rate per unit area of ​​the cylindrical slices with different reaction times; record the surface morphology and microscopic characteristics of rock thin slices of special thickness after the dissolution experiments with different reaction times.

[0046] Furthermore, petrological parameters of carbonate reservoirs are rock type, mineral composition, pore type and pore structure.

[0047] Furthermore, carbonate rock samples consistent with the target reservoir in the study area are selected based on petrological parameters; the type and concentration of diagenetic fluids used in the experiment are mainly determined based on the fluid history of the study area; and the selection of experimental conditions during carbonate rock dissolution must be closely integrated with the geological background of the study area.

[0048] Furthermore, the diameter of the cylindrical slice is 2.5-3cm and the thickness is 0.3-0.5cm; the thickness of the special thickness rock slice reaches 100-300μm, which can ensure observation under a microscope without affecting the dissolution reaction.

[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0050] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0051] Example 1

[0052] A dissolution experimental method for synchronously observing dissolution rate and structure, comprising the following steps:

[0053] In order to study the difference of dolomite dissolution, in addition to the algal dolomite of group D in this area, the dolomite samples of area A and area B Carboniferous dolomite were also collected for comparative analysis; the thin section identification of dolomite lithology is algal sand-clastic dolomite, algal stromatolite, algal stromatolite, algal dolomite, algal clot dolomite, fine-medium crystalline dolomite and fine-crystalline dolomite. The typical core photos of the dissolution experimental samples are shown in Figure 1. Figure 2 shown.

[0054] S1: According to previous studies, the dolomite in Group D of the study area is mainly affected by exposed karst, so the temperature and pressure settings do not need to be set too high. Therefore, the experimental temperature of this indoor dissolution experiment is set at 50°C and 0.3Mpa in a rotary high-temperature and high-pressure reactor with a rotation speed of 60 rpm. The experiment mainly compares the effects of different lithologies and structures on dissolution, so each group of experiments uses the same temperature, pressure and fluid conditions.

[0055] S2: In order to speed up the experimental progress, a hydrochloric acid aqueous solution with a pH of 4 was used as the experimental fluid;

[0056] S3: Each sample is processed into two types: cylindrical slices and rock slices of special thickness;

[0057] S4: Use a vernier caliper to measure the diameter and thickness of each cylindrical slice at different positions, and calculate the average value, and then calculate the surface area of ​​each cylindrical slice. The calculation results of the diameter, thickness and surface area of ​​the dissolution test samples are shown in Table 1;

[0058] Table 1 Calculation results of diameter, thickness and surface area of ​​experimental samples

[0059] serial number Lithology Strata Diameter(cm) Thickness(cm) <![CDATA[Surface area (cm 2 )]]> GS1 Algal dolomite Group D 2.81 0.38 15.77 GS2 Algal stromatolite Group D 2.81 0.39 15.84 GS3 Algal stromatolite Group D 2.82 0.42 16.17 MX1 Algal dolomite Group D 2.51 0.52 13.98 MX2 Algae clot dolomite Group D 2.42 0.47 12.81 MX3 Algae clot dolomite Group D 2.42 0.64 14.04 MX4 Fine-medium crystal dolomite A Region Group 2.82 0.42 16.15 HD1 Fine-grained dolomite Carboniferous 2.80 0.40 15.89

[0060] S5: Wash the cylindrical slices with ultrapure water and dry them in a constant temperature drying oven for 2 hours at a set temperature of 105°C; after drying, cool the samples in a drying dish and weigh each cylindrical slice with an analytical balance;

[0061] S6: Use a camera to take pictures of each cylindrical slice; use a polarizing microscope to observe the microscopic characteristics of each slice, including composition, structure, pores and crack development;

[0062] S7: placing the cylindrical slices and thin slices in the sample tray of the reaction pot, introducing a hydrochloric acid aqueous solution with a pH value of 4 into the reaction pot, setting the temperature to 50° C. and the pressure to 0.3 MPa to conduct a dissolution experiment;

[0063] S8: After the dissolution experiment was carried out for 1 h, 2 h, 3 h, 6 h, 12 h, 15 h, 21 h, 27 h, 37 h, 165 h and 235 h, the samples were taken out and steps S5, S6 and S7 were repeated to record the weight, surface morphology and microscopic characteristics of the samples after dissolution at different times (e.g. Figure 3 , Figure 4 and Figure 5 The dissolution rate per unit area of ​​the cylindrical slices with different reaction times is calculated, and the calculation results of the dissolution rate are shown in Table 2. The above method realizes the synchronous observation of the dissolution rate and the microscopic morphology.

[0064] Table 2 Calculation results of experimental sample formation, lithology and dissolution rate

[0065]

[0066] The results of the dissolution experiment in this example show that:

[0067] (1) Figure 3 As shown, the dissolution start-up rate of all samples is high, and as the dissolution time increases, the dissolution rate decreases significantly and tends to be stable;

[0068] (2) Figure 4 As shown in the figure, the dissolution rates of different samples are significantly different. The dissolution rates of algal stromatolite and algal sand-clastic dolomite are the highest, followed by algal clot dolomite, and the dissolution rate of algal stromatolite is the lowest.

[0069] (3) Figure 5 As shown in the figure, by observing and comparing the microscopic dissolution characteristics of samples at different reaction times, it was found that the degree of dissolution along the intergranular and intercrystalline pores and microcracks was high.

[0070] (4) Figure 6 As shown, the development of the D group algal dolomite reservoir may be related to the dissolution of interalgal dolomite.

[0071] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A dissolution experimental method for synchronous observation of dissolution rate and structure, characterized in that: The following steps are involved: S1: Analyze the actual geological background, determine the simulated experimental samples and prepare the experimental fluid; S2: Processing the determined simulated experimental samples into cylindrical slices and rock slices of special thickness respectively; then measuring and calculating the parameters of each cylindrical slice; S3: Record the surface morphology and microscopic features of cylindrical slices and rock thin sections of special thickness respectively; S4: After subjecting the cylindrical slices and rock slices of special thickness in S2 to dissolution simulation experiments with different reaction times in the prepared experimental fluid, the parameters of the cylindrical slices after the dissolution simulation experiments with different reaction times are measured and calculated to obtain the dissolution rate per unit area of ​​the cylindrical slices with different reaction times; the surface morphology and microscopic characteristics of the rock slices of special thickness after the dissolution simulation experiments with different reaction times are recorded.

2. A dissolution experimental method for synchronous observation of dissolution rate and structure according to claim 1, characterized in that: In S1, the actual geological background includes petrological parameters and geological fluid characteristics of the carbonate reservoir.

3. A dissolution experimental method for synchronous observation of dissolution rate and structure according to claim 2, characterized in that: The simulation experiment samples are determined according to the petrological parameters of the carbonate reservoir.

4. A dissolution experimental method for synchronous observation of dissolution rate and structure according to claim 3, characterized in that: The petrological parameters of the carbonate reservoir are rock type, mineral composition, pore type and pore structure.

5. A dissolution experimental method for synchronous observation of dissolution rate and structure according to claim 4, characterized in that: Prepare experimental fluids according to the characteristics of geological fluids.

6. The method for dissolution experiment for simultaneous observation of dissolution rate and structure according to claim 1, characterized in that: In S2, the diameter of the cylindrical slice is 2.5 to 3 cm, and the thickness is 3 to 5 mm; the thickness of the special thickness rock slice is 100 to 300 μm.

7. The method for dissolution experiment for simultaneous observation of dissolution rate and structure according to claim 1, characterized in that: The parameters are the weight and the surface area of ​​the cylindrical slice.

8. A dissolution experimental method for synchronous observation of dissolution rate and structure according to claim 7, characterized in that: Before measuring the weight of the cylindrical slice, the cylindrical slice is washed with ultrapure water and then dried; The calculation process of the surface area of ​​the cylindrical slice is as follows: the diameter and thickness of each cylindrical slice at different positions are measured with a vernier caliper, and the average value of the diameter and thickness is obtained, and then the surface area of ​​each cylindrical slice is calculated.

9. The method for dissolution experiment for simultaneous observation of dissolution rate and structure according to claim 1, characterized in that: The microscopic characteristics include mineral composition, surface structure, pores and crack development; the surface morphology is obtained by observing with a polarizing microscope.

10. The method for dissolution experiment for simultaneous observation of dissolution rate and structure according to claim 1, characterized in that: In S4, the temperature of the dissolution simulation experiment is 50-100° C., the pressure is 0.1-0.4, and the time is 1-240 hours.

Citation Information

Patent Citations

  • Analysis method of corrosion action and corrosion effect of carbonate rock

    CN104407118A